Model for the Erosion Rate Curve of Cohesive Soils. Issue 1 (January 2017) - Rahimnejad, Reza; Ooi, Phillip S. K.
The scour rate found by the cohesive soil-erosion function apparatus (SRICOS-EFA) method provides more accurate and realistic scour predictions than the Richardson and Davis equation, which tends to overpredict scour, especially in cohesive soils. Scour of cohesive soil occurs more slowly than scour of cohesionless soils. The time-dependent nature of scour of cohesive soils can be understood by considering both the variation of flood intensity over time and the scour characteristics of the soil, with an erosion rate curve obtained with an erosion function apparatus (EFA). One drawback of the SRICOS-EFA method is that the EFA requires a significant cost outlay. A model for the erosion rate curve is proposed on the basis of EFA tests conducted on 31 undisturbed fine-grained soils from five water channels on the island of Oahu, Hawaii. A hyperbolic regression model was developed with four explanatory variables: water content, liquid limit, plasticity index, and activity, which are easily measured in the laboratory. Parameter estimates for the model were then obtained using nonlinear ordinary least squares. A key element of the model is that the parameter estimates logically affect the sign and magnitude of critical shear stress, in accord with observed soil behavior—that is, it was found that the model captured the effects of water content and plasticity index on the critical shear stress quite effectively. Also, the model provided reasonable estimates of the 31 erosion rate curves. Use of this model in the SRICOS-EFA method to estimate scour depth can result in less scour and can result in significant bridge cost savings.